(3eWdY GdHOhQs - (3Gdjefj, , Uaj GdOjf, CMeO Hf UGdM Hf CHj GdQLGd, J(B1092 (3g`s
(3ChdgG (B:s
(3HSe Gddg (B... (3MQa GdWGA GdegedI ; GdSjO GdWGgQ Hf jMji Hf GdMSf jf LYaQ Hf YHO Gddg Hf GdMSjf Hf Ydj Hf GdMSjf Hf Ydj Hf CHj WGdH Ydjg GdSdGe (B...s
(3BNQgG (B:s
... (3GdMSjf Hf YjSi Hf eMeO Hf LYaQ GdbGSej QMeg Gddg (B... (3abg eJcde Jhaj HGdQj SfI SJ hYTQjf hKdGK eGFI QMeg Gddg , GfJgi GdLRA GdKGdKs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe , ddRQcdj (B1/137s
(3EjVGM Gdecfhf (B2/500s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJGQjNs